Kondisi lingkungan fisik dan lama waktu bermain di luar rumah dengan kegemukan pada anak prasekolah - Ika Agustina; I Made Alit Gunawan; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: The prevalence of childhood obesity in Yogyakarta Municipality has increased in recent years. The built environment of which are not designed properly may limit the time for children's outdoor activity.Objective: This study tried to investigate the links between parents perceptions of their built environment with outdoor playing time and obesity among preschool children in Yogyakarta Municipality.Method: This is a case-control study. Cases were identified as obese preschoolers (Z score based on W / H> 2 SD) and controls were children who were not obese (Z score based on W / H ≤ 2 SD) and matched by sex and age. Data were collected in the Yogyakarta Municipality. Samples were selected using multistage sampling method. The sample of cases and controls were 101 people (1: 1), respectively. conditional logistic regression statistical tests were performed to identify the risk factors for preschool obesity.Results: Children who did not play outdoors enough time were at higher risk of becoming obese (OR = 2,27, CI (1,14-4,62)); Built environment seems to be a modifier for outdoor playing time that will impact the odds of obesity among preschool children. Conclusion: Preschool children who played outdoor less than 2 hours had a higher risk of becoming obese. Outdoor playing time was associated with built environment.